The Impact of Position Levels on Time Discipline Among Kitchen Department Employees at The Westin Hotel Jakarta - Marya Yenny; Abi Sapta Dinata; Richie Perdana Putra; racia Diva Kusumastuti (The Postgraduate School of Tourism Sahid Polytechnic, 2024)
Purpose: This study aims to examine the relationship between job levels and time discipline among employees in the kitchen department at The Westin Jakarta Hotel. Research method: A Quantitative-Descriptive approach was employed, utilizing a questionnaire to gather data. The collected data was analyzed using SPSS software. Results and discussion: The findings reveal that time discipline issues persist, particularly among employees at the Sous Chef level, who accumulated approximately 1,004 minutes of tardiness in a single month. Implications: The study concludes that job level does not significantly influence time discipline, highlighting that punctuality issues are prevalent across various job positions.